Family income and nutrition-related health: Evidence from food consumption in China. (July 2019) - Ren, Yanjun; Li, Hui; Wang, Xiaobing
Abstract: With increasing family income, the prevalence of overweight has risen and become a serious threat to individual health and a major public health challenge in China. This study attempts to shed light on the mechanism of income impact on the adult health outcomes of BMI and overweight through five potential channels: nutritional intakes, dietary diversity, dietary knowledge, food preference, and dining out. Using the panel data from the China Health and Nutrition Survey (CHNS), we investigate the causal relationship between income and health by considering the changes in the minimum wage as a valid instrument to address the endogeneity problem of income in health estimation. The results indicate that rising income increases the adults' BMI and the propensity to be overweight; approximately 15.58% and 16.20% of income impact on BMI and overweight could be explained by the five channels considered, respectively. Among the five channels, dietary diversity plays the most significant role in explaining the income impact. We observe significant heterogeneity in income-BMI gradients across various income quantiles and subsamples. Specifically, income-BMI gradients tend to increase along with income percentiles, and income has a significantly positive impact on BMI and overweight for the male sample but it shows no significant impact for the female sample. Highlights: Five important mechanisms of income impact on BMI and overweight are highlighted. The endogeneity of income is addressed by using minimum wage as an instrument. Rising income increases the adults' BMI and the propensity to be overweight. Dietary diversity plays the most significant role in explaining the income impact.